PENGARUH KUALITAS PRODUK, HARGA, DAN PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN INTRAOCULAR LENS PADA PT. GAUDIUM VITAE, JAKARTA - Furkon, Acep Muhamad; Basri, Har Adi (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
This study aims to determine the effect of the product quality,price and personal selling on purchasing decisions product intraocular lens at Gaudium Vitae company. The low intraocular lens purchase decision on PT. Gaudium Vitae from year to year and the problem of product quality, prices that are still felt by some consumers and personal selling which are still obstacles is the background in this research. The independent variable product qaulity, price and personal selling affect the purchase decision as the dependent variable. The population in this study were consumers of Gaudium Vitae. Samples were taken of 42 respondents method through angket filled out by customers. Then, the data obtained were analyzed using mutltiple linier regression analysis. This analysis includes the validity test, descriptive statistical test, classic assumption test, hypothesis test. Based result, obtained regression equation: Y = -2,130 + 0,724 X1 + 0,152 X2 + 0,207 X3. The result of research both partially and simultaneously the quality product, price and personal selling have a positive and significant effect on purchasing decisions.